“Yeah, I Know You Always Stay”: Menjelajahi Dunia Virtual ARMY pada Fanbase @bitiesfess Selama Hiatus Grup - Meilya Syifa Aghniya Rahman; Zainal Abidin Achmad (Jurnal Sosial Humaniora, 2024)
Cultural researchers have long been concerned about the development of KPop fan activities. ARMY fandom stands out as a unique research subjectbecause this community has its style of expressing feelings and admiration forBTS. Within a virtual community of fans (fanbase), ARMY fandom gathersand interacts actively. ARMY Indonesia actively builds fan closeness,exemplified by the @bitiesfess fanbase. Even when the group undergoesmilitary service (hiatus), ARMY Indonesia actively communicates andsupports BTS. Researchers analyzed fan interactions using a virtualethnographic approach. The research results reveal four key areas of fandominteraction in the @bitiesfess fanbase: 1) The communication area activelysegments into four forms: real-time updates, fan jokes, nostalgia, andexposure. 2) The fanbase's creativity field actively comprises various fan editsand memes. 3) The field of knowledge during the hiatus period activelydominates with activity schedules, member updates, education, advice, andfun facts. 4) The organization and civil power field actively invite followers tosupport movements, e.g., streaming, philanthropy, reporting and blocking,and advocacy campaigns.